PBEF/NAMPT/visfatin: a promising drug target for treating rheumatoid arthritis?. (April 2012) - Nowell, Mari; Evans, Laura; Williams, Anwen
NAMPT, also known as pre-B-cell colony-enhancing factor and visfatin, has been proposed to be involved in preventing apoptosis in cancer cells and, as such, has received a great deal of attention in recent years and stimulated the development to specific inhibitors for treating cancer. The role of NAMPT inhibitors as potential therapeutic agents for other diseases has not been studied extensively. Here, we describe their applicability for treating rheumatoid arthritis. We summarize current knowledge of NAMPT expression in healthy and diseased tissues, thereafter, we focus on pathological mechanisms relevant to rheumatoid arthritis that involve the NAMPT pathway and review the current status of NAMPT inhibitors being evaluated in clinical trials.